PENGARUH PERSEPSI KUALITAS TERHADAP MINAT KUNJUNGAN ULANG (SURVEI PADA PENGUNJUNG WISATA MANGROVE SEDARI KARAWANG) - Novia Krisdyawati; Abdul Yusuf (The Asia Pacific Journal Of Management Studies, 2021)
Revisit interest is the desire of tourists to visit tourist destinations with similarities the second time. The decision on the interest in revisiting is in the hands of the tourist. Tourists pay attention to various things that can be done as they wish. Perceptions of quality are customer assumptions that can be considered on quality that is not good, goods or services that are not desirable. If the assumption is good, then the goods or services will last a long time. In order for tourists to have a positive perception, the Sedari Mangrove Tourism must present attractions at its tourist attractions. Tourist attractions are all that are owned, of good value or diversity or the acquisition of motivated tourists to visit these tourist attractions. Sedari Mangrove Tourism seeks to present attractions, including water bikes, a place to take pictures decorated with beautiful umbrellas on it. With these attractions, it is expected that visitors will feel satisfied and happy. This research aims to determine, explain and analyze the effect of perceived quality and value perceptions on the interest of revisiting surveys on mangrove tourism in Sedari, Karawang. This research was conducted using descriptive and verification methods. The sampling technique used is the Random Sampling technique with a sample size of 335 respondents and processed using SPSS16. The results of this study indicate that perceived quality has an effect on revisit interest with a value. (0.000) <α (0.05) and tcount (11.237)> ttable (1.976). Perceived Value affects Revisit Interest with a sig. (0.000) <α (0.05) and tcount (8.874)> t table (1.976). Perceptions of Quality and Perceptions of Value affect the Interest of Revisits with a sig. (0.000) <α (0.05) and fcount (786.303)> ftabel (3.02). The results of the coefficient of determination show that Revisit Interest (Y) is influenced by Perceptions of Quality (X1) and Perceptions of Value (X2) of 82.6%, the remaining 17.4% is influenced by other variables..